"Likes" as KPI: An examination of teenage girls' perspective on peer feedback on Instagram and its influence on coping response. Issue 7 (October 2018) - Li, Pengxiang; Chang, Leanne; Chua, Trudy Hui Hui; Loh, Renae Sze Ming
Highlights: The perspectives of teenage girls on peer feedback on Instagram were explored. SEM was employed to reflect the relationships between peer feedback, self-esteem, depressed mood, and coping strategies. Teenage girls placed greatest importance on attaining likes. Problem-focused and emotion-focused coping were concomitantly adopted to handle the involved stress. Abstract: Through a survey of 296 female students in Singapore aged 12–18 years regarding their selfie-posting behaviors on Instagram, this study explored teenage girls' perspectives on the importance of receiving peer feedback on selfies. The associations between peer feedback importance and self-esteem as well as depressed mood were also examined. Drawing on coping theory, this study further investigated how the importance of peer feedback and depressed mood influence girls' coping responses to the stress from lacking feedback. The results of structural equation modeling demonstrate that self-esteem exerts a negative effect on the importance of peer feedback and depressed mood, but the importance of peer feedback is positively associated with depressed mood. In addition, both the importance of peer feedback and depressed mood positively impact problem-focused and emotion-focused coping strategies. The results suggest that peer feedback has become a "KPI" of selfie-posting behaviors for teenage girls, and these girls handle the involved stress by a concomitant adoption of both types of coping.